Neuroprotective Effects of Exogenous Irisin in Kainic Acid-Induced Status Epilepticus - Cheng, Yao; Cui, Yaru; Zhai, Yujie; Xin, Wenyu; Yu, Yan; Liang, Jia; Li, Shucui; Sun, Hongliu (Frontiers in Cellular Neuroscience, 2021)
Elevated reactive oxygen species (ROS) level is considered a crucial causative factor for neuronal damage in epilepsy. Irisin has been reported to ameliorate mitochondrial dysfunction and to reduce ROS levels; therefore, in this study, the effect of exogenous irisin on neuronal injury was evaluated in rats with kainic acid (KA)-induced status epilepticus (SE). Our results showed that exogenous irisin treatment significantly increased the expression of brain-derived neurotrophic factor (BDNF) and uncoupling protein 2 (UCP2), and reduced the levels of neuronal injury and mitochondrial oxidative stress. Additionally, an inhibitor of UCP2 (genipin) was administered to investigate the underlying mechanism of irisin-induced neuroprotection; in rats treated with genipin, the neuroprotective effects of irisin on KA-induced SE were found to be partially reversed. Our findings confirmed the neuroprotective effects of exogenous irisin and provide evidence that these effects may be mediated via the BDNF/UCP2 pathway, thus providing valuable insights that may aid the development of exogenous irisin treatment as a potential therapeutic strategy against neuronal injury in epilepsy.